Treatment of acute myocardial infarction with anisoylated plasminogen streptokinase activator complex. Issue 6550 (27th September 1986) - Ikram, S; Lewis, S; Bucknall, C; Sram, I; Thomas, N; Vincent, R; Chamberlain, D
Abstract : A controlled trial in 149 patients admitted to a district hospital with probable myocardial infarction tested the effect of 30 units of anisoylated plasminogen streptokinase activator complex (APSAC) on indices of infarct size. Patients were grouped prospectively according to whether they entered the trial within two and a half hours (early entry) or between two and a half and four hours (late entry) after onset of the symptoms. Sixty seven of 73 patients in the control group showed increased plasma activity of myocardial creatine kinase isoenzyme that was diagnostic of infarction compared with only 60 of 76 who received APSAC. The difference was significant overall but occurred predominantly in the early entry group. The patients who received APSAC had more early ventricular arrhythmias, compatible with reperfusion, and showed greater preservation of R waves during admission to hospital. Unwanted effects were generally minor and more common in the actively managed group than the control group (26% v 3%). After nine to 12 months of follow up 12 patients in the control group had died compared with seven in the actively managed group. The ease of administration and the apparent efficacy of APSAC suggest that it is suitable for use in a district hospital for patients with suspected acute myocardial infarction.